Assault on Iwo Jima [videorecording (DVD)]. (A & E Television Network, 2007)
On February 19, 1945, the 3rd, 4th, and 5th Marine Divisions stormed Iwo Jima's heavily defended shores in what was supposed to be a three or four day battle, instead, the siege went on for 36 days.